2021
DOI: 10.3390/ijerph18126669
|View full text |Cite
|
Sign up to set email alerts
|

Costs for Statutorily Insured Dental Services in Older Germans 2012–2017

Abstract: Objectives: We assessed the costs of dental services in statutorily insured, very old (geriatric) Germans. Methods: A comprehensive sample of very old (≥75 years) people insured at a large Northeastern statutory insurer was followed over 6 years (2012–2017). We assessed dental services costs for: (1) examination, assessments and advice, (2) operative, (3) surgical, (4) prosthetic, (5) periodontal, (6) preventive and (7) outreach services. Association of utilization with: (1) sex, (2) age, (3) region, (4) socia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…However, it is unclear what kind of dental treatment the respondents could not afford. This would be important information, as in Germany the amount of costs for these treatments can certainly vary [ 80 ]. Moreover, it is important to note that functional limitations such as reduced chewing ability are an integral component of the broader concept of oral health-related quality of life (OHRQoL) [ 81 ] that can be assessed, for example, with the OHIP-5 (Oral Health Impact Profile) [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear what kind of dental treatment the respondents could not afford. This would be important information, as in Germany the amount of costs for these treatments can certainly vary [ 80 ]. Moreover, it is important to note that functional limitations such as reduced chewing ability are an integral component of the broader concept of oral health-related quality of life (OHRQoL) [ 81 ] that can be assessed, for example, with the OHIP-5 (Oral Health Impact Profile) [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that several factors were associated with the financial burden of healthcare, such as household size, presence of family members aged over 65, household members with a chronic disease, income, absence of health insurance, and education level [ 1 , 5 , 6 ]. The financial burden of healthcare is widely spread among older people in European countries, and the cross-country differences in the distribution of financial burden highlighted the importance of identifying people who are vulnerable [ 4 , 7 , 8 ]. This was mainly due to medicines, medical products, outpatient and inpatient care, and diagnostic tests [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The population is aging all over the world, and it is estimated that in European countries, the share of people over 65 years will grow from 19.1% in 2020 to 30.4% of the total population by 2100, or even more, such as in Slovenia (31.4%,), Serbia (34.4%), and Croatia (35.1%) [ 20 ]. Among persons aged over 65, multimorbidity and frailty increase the risk of the financial burden of healthcare as well as the presence of some chronic disease or cancer does, when in need of more contact with the health system and prescribed medicines [ 4 , 6 , 7 , 8 , 21 , 22 , 23 , 24 ]. There appears to be no research that has evaluated the older-aged population’s experiences related to the financial burden of medical care, dental care, and medicines in Slovenia, Serbia, and Croatia using specific and comparable data.…”
Section: Introductionmentioning
confidence: 99%